The effect of bonding agents on the microleakage of sealant following contamination with saliva - Askarizadeh Nahid; Norouzi Negar; Nemati Saeed (Wolters Kluwer Medknow Publications, 2008)
Aims : An issue of concern in dentistry is the inadequacy of adhesion and proper sealing following restoration of a tooth, which can lead to marginal leakage. The aim of this study was to evaluate the effect of a bonding agent on the microleakage of a sealant material following contamination with saliva. Materials and Methods : In this experimental research, 48 sound premolars were divided into two groups. The first group received sealant without bonding and the other group was given sealant with bonding. After prophylaxis, the occlusal surfaces were etched with 37% phosphoric acid gel and the teeth were then placed in fresh human saliva for l0 s. Following this, in the first group fissure sealant (Kerr) was applied directly and cured; for the second group sealant was placed and cured after bonding (Single Bond; 3M). All samples were thermocycled (500 cycles; between 5°C and 55°C; dwell time of 30 s). Silver nitrate was used as the leakage tracer. The teeth were sectioned. Microleakage evaluation was made by stereomicroscope at 40x magnification and the results were evaluated with the Mann-Whitney U test. Results : In the group that received sealant without bonding extensive microleakage was seen; placement of sealant with bonding significantly reduced microleakage. Conclusion : In the presence of contamination with saliva, use of bonding under the fissure sealant can reduce microleakage